Development of Geogebra Applets of Equation and Square Functions for Class Ix Students of Junior High School - Sudarsana, Made; Hartawan, I Gusti Nyoman Yudi (Jurnal Pendidikan MIPA, 2022)
The purpose of this research is to make learning media that meet the quality requirements of learning media. There are three objectives targeted in this study, namely, Knowing the characteristics of the media, knowing the practicality, and knowing the effectiveness of the media. This type of research is research and development using a 4-D development model. The stages of developing the 4-D model used include the definition stage, the design stage, and the development stage. These stages produce GeoGebra applet learning media which consists of 3 applet media that have been tested for feasibility with an average of 4.48 in the Very Eligible criteria. The learning media produced have been tested for their practicality, seen from the results of the analysis of the average teacher response questionnaire scores and student responses, which are 5.0 and 4.5 which have a very good practicality level. And this media has been proven effective in learning. This can be seen from the classical completeness with the percentage of classical completeness 84.37%. The conclusion is that the GeoGebra applet learning media is practical and effective to train students' conceptual understanding IX grade junior high school on equations and quadratic functions Keywords: GeoGebra applet, 4-D development model, quadratic equations and functions. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1241-1251